Interpreting complex fluvial channel and barform architecture: Carboniferous Central Pennine Province, northern England. Issue 1 (January 2016) - Soltan, Roman; Mountney, Nigel P.
Abstract: The Bashkirian Lower Brimham Grit of North Yorkshire, England, is a fluvio‐deltaic sandstone succession that crops out as a complex series of pinnacles, the three‐dimensional arrangement of which allows high‐resolution architectural analysis of genetically‐related lithofacies assemblages. Combined analysis of sedimentary graphic log profiles, architectural panels and palaeocurrent data have enabled three‐dimensional geometrical relationships to be established for a suite of architectural elements so as to develop a comprehensive depositional model. Small‐scale observations of facies have been related to larger‐scale architectural elements to facilitate interpretation of the palaeoenvironment of deposition to a level of detail that has rarely been attempted previously, thereby allowing interpretation of formative processes. Detailed architectural panels form the basis of a semi‐quantitative technique for recording the variety and complexity of the sedimentary lithofacies present, their association within recognizable architectural elements and, thus, the inferred spatio‐temporal relationship of neighbouring elements. Fluvial channel‐fill elements bounded by erosional surfaces are characterized internally by a hierarchy of sets and cosets with subtly varying compositions, textures and structures. Simple, cross‐bedded sets represent in‐channel migration of isolated mesoforms (dunes); cosets of both trough and planar‐tabular cross‐bedded facies represent lateral‐accreting and downstream‐accreting macroforms (bars) characterized by highly variable, yet predictable, patterns of palaeocurrent indicators. Relationships between sandstone‐dominated strata bounded by third‐order and fifth‐order surfaces, which represent in‐channel bar deposits and incised channel bases, respectively, chronicle the origin of the preserved succession in response to autocyclic barform development and abandonment, major episodes of incision probably influenced by episodic tectonic subsidence, differential tilting and fluvial incision associated with slip on the nearby North Craven Fault system. Overall, the succession represents the preserved product of an upper‐delta plain system that was traversed by a migratory fluvial braid‐belt system comprising a poorly‐confined network of fluvial channels developed between major sandy barforms that evolved via combined lateral‐accretion and downstream‐accretion.